Effects of ambient lighting conditions on the scanning accuracy and shade matching capability of intraoral scanners: an in vitro study - Yongqing Guo; Yun Ma; Zien Wang; Hao Yu (BMC Oral Health)
Abstract Background Ambient lighting conditions has been confirmed as a significant factor influencing scanning performance. However, research on the optimal levels of both illuminance and color temperature for the scanning accuracy and shade matching capability of intraoral scanners (IOSs) remains limited. This study aimed to evaluate the impact of illuminance and color temperature levels on the scanning accuracy and shade matching capability of IOSs. Methods Ten maxillary typodonts were prepared, each featuring a right central incisor replaced by shade tabs from Vita toothguide classical (VC) and Vita toothguide 3D-Master (VM) shade guides. The right lateral incisor and left second premolar of each typodont were prepared. A laboratory scanner (InEos X5, Dentsply Sirona) was utilized to digitize the typodonts, creating a reference standard tessellation language (STL) file. The typodonts were then scanned using two IOSs (Trios 4 wireless, 3Shape A/S; Primescan, Dentsply Sirona) under different illuminance levels (0, 500, 1000, and 2500 lx) and color temperatures (4100, 5500, and 6500 K) to generate experimental STL files. Then, the scanning accuracy (trueness and precision) and shade matching capability (accuracy and repeatability) were also calculated. Results Illuminance significantly influenced the scanning accuracy of the IOSs tested, whereas color temperature significantly affected shade matching outcomes (P < 0.05). The best scanning trueness was observed for Trios 4 at 1000 lx, while Primescan showed the best scanning trueness and precision at 2500 lx. Regarding shade matching capability, Trios 4 achieved the highest accuracy and repeatability at 5500 K, while Primescan performed best at 4100 K in terms of accuracy and repeatability. Conclusions Ambient lighting conditions significantly influenced the performance of IOSs. Trios 4 demonstrated optimal outcomes at 1000 lx and 5500 K, whereas the highest accuracy was attained for Primescan at 2500 lx and 4100 K. This study highlights the importance of optimal ambient lighting conditions to enhance the performance of IOSs.